Potencial evocado auditivo de longa latência e frequency following response: uma análise de associação e correlação em adultos jovens - Betti, Tainá (2021)
The sound stimulus is transformed into an electrical stimulus by the internal hair cells of the cochlea and conducted to the auditory cortex by means of neural synapses. These, in turn, are evaluated by the Hearing Evoked Potentials, responsible for informing about the integrity and functionality of the central auditory pathway. Among the potentials, the Long Latency Auditory Evoked Potential (LLAEP) investigates the auditory perception of the sound stimulus, as well as abilities such as attention and memory, covering subcortex and cortex structures. Frequency Following Response (FFR) is responsible for the evaluation of the entire central auditory pathway, exposing the coding of verbal sounds by the system. Accordingly, the objective of this study is to correlate and associate the findings of LLAEP and FFR in normal6hearing young adults, taking into account the latency values of the potentials. It is a prospective, cross6sectional, quantitative and qualitative study with a sample of convenience involving normalized or normal adults. The individuals underwent anamnesis, meatoscopy, threshold and vocal audiometry, acoustic immittance measurementsj Digits Dichotic Test (TDD) and Randon Gap Detection Test (RGDT)j Brainstem Auditory Evoked Potential (BAEP) for sample composition. As research procedures, the Frequency Following Response (FFR) and Long Latency Auditory Evoked Potential (LLAEP) were performed. Two expert judges performed the analysis of the examinations. The significance used was 5%. The sample consisted of 32 individuals (20 women and 12 men) normal6hearing adults, with a mean age of 22.5 years (18 and 32 years) with normality in BAEP, RGDT and TDD. Positive correlation between VA complex and P1 wave with values from to de r=0,52(p6 value=0,007) e A/P1 de r=0,64(p6value=0,001) and negative with N2 being V/N2 r=60,47(p6 value=0,015) e A/N2 r=60,44(p6value=0,023) and still positive correlation of C with N2 with values of r=0,43(p6value=0,036) statistically significant was observed. There was no significant association between normal and altered individuals in the tests in general and when associated by components. In conclusion, FFR presents correlation with some LLAEP waves, which reinforces the hypothesis that there is contribution of different cortical areas to the formation of FFR waves. No association was observed between the qualitative results of the tests, demonstrating the impartiality of each test.